Rethinking Parliamentary Status: Are Parliamentarians Bound by the Protected Disclosures Act 2000? A Comparison Between South Africa and New Zealand - Hilton, Luke (Victoria University of Wellington Law Review, 2018)
This article compares the Protected Disclosures Act 2000 (PDA) in South Africa and New Zealand. The comparison is framed by the question whether the PDA binds members of Parliament (MPs) or not. Regarding South Africa, the article analyses the provisions of the PDA and its curial interpretation in the Charlton litigation. Technically, MPs are bound by the PDA. This article nonetheless defends the Labour Appeal Court’s merits judgment, which held that MPs are not bound. Regarding New Zealand, the article analyses the provisions of the PDA and suggests the probable outcome in court if similar litigation were ever to occur in New Zealand.